Evidence Based Practice in Juvenile Justice: Nebraska White Paper - Hobbs, Anne M. (2014)
This White Paper is the product of the collaborative effort of the University of Nebraska/Lincoln (UNL) Law and Psychology Program, the University of Nebraska/Omaha (UNO) Consortium for Crime and Justice Research and the UNO Juvenile Justice Institute. The purpose of this paper is to provide an overview for understanding, testing, and developing Evidence Based Practice (EBP) interventions that make rehabilitative services available to children in the juvenile justice system. The paper begins with a summary of a proposal for a classification system of EBP programs in the Juvenile Justice System in Nebraska and then goes on to explain the logic of the classification system.